Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PAI Kelas VIII Di SMPN 2 Mapat Tunggul Dengan Penerapan Metode Pendekatan PJBL ( Project Based learning ) - Junid, Yan (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to determine the impact of applying the Project-Based Learning (PJBL) approach in improving students’ learning outcomes on the topic "Inspiration from the Quran, the Beauty of Practicing Religion Moderately" in grade VIII. The study was conducted in two cycles, the first and second cycles. In the first cycle, students showed improvement in learning outcomes, though not all reached the Minimum Completeness Criteria (KKM). After evaluation and adjustments, the second cycle showed significant improvement in students’ learning achievements, as seen in the increased number of students who met the KKM. This study indicates that the use of the PJBL approach can enhance students’ motivation, engagement, and understanding of the material. Thus, the PJBL approach is proven to be effective in improving the quality of Islamic Religious Education learning.